La protección penal de la seguridad e higiene en el trabajo - Garcia Cavero, Percy (Revista de Derecho, 2019)
The present article deals with the offense of non compliance with the duty of prevention of occupational risks recently incorporated in article 168-A of the Penal Code. Although it is a significant step in the protection of workers safety and health, the penal type contains certain particularities that influence on the penal ascription of this offense to employers or people in charge who break the duty of prevention. On one hand, the penal type goes back to the labor norm on safety and hygiene at work to determine who might be the author of the offense and when a behavior reaches penal relevance, which makes it a blank criminal law. On the other hand, the configuration of the offense is produces with a risk on the life or health of workers, assuming the structure of an offense of concrete danger.